To the problem of structurally-substantial and functional components of the personal activity - Т S Medvedskaya (Peoples' Friendship University of Russia (RUDN University), 2009)
The article is devoted to the interrelation of structurally-substantial and functional components of personal activity. It is analyzed the personal efforts efficiency's degree in overcoming stressful situation depending on activity components.